Resource allocation during the transition to a market economy policy implications of supply bottlenecks and adjustment costs - Aizenman, Joshua 1949-; Isard, Peter (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1993)
This paper explains why a laissez-faire approach may fail to account for externalities in transforming economies, focusing on externalities associated with supply bottlenecks and adjustment costs. Bottlenecks tend to arise whenever input requirements are stochastic and the opportunity cost of holding inventories is high. They are likely to become prevalent in the state industrial sector once budget constraints are hardened and credit markets begin to function properly, since the creditworthiness of state enterprises is limited by outdated production technologies. The analysis recognizes that producers have incentives to form pooling arrangements, supported potentially by market mechanisms, for reallocating stocks of critical inputs. It is shown, however, that such arrangements do not eliminate the externalities, and that the externalities rise in a nonlinear manner with the opportunity cost of holding inventories. The analysis suggests that once budget constraints are hardened, the externalities associated with bottlenecks and adjustment costs provide a case for subsidizing the costs of critical inputs for the state industrial sector, but not for the new private sector. This subsidy declines as the private sectors grows.